486Serum levels of miRNA-221 and -222 may be predictive biomarkers for cognitive decline. (2nd September 2021) - Ishihara, Yuya; Yamada, Hiroya; Munetuna, Eiji; Hagiwara, Chiharu; Fujii, Ryosuke; Yamazaki, Mirai; Hatta, Takeshi; Iwahara, Akihiko; Ohashi, Koji; Ishikawa, Hiroaki; Ando, Yoshitaka; Mizuno, Genki; et al.
Abstract: Background: Although dementia is a huge problem in public health, no fundamental biomarker has been established to detect cognitive decline at the early stage. MicroRNAs (miRNAs) regulate gene expression, and are associated with the development of various diseases. Methods: The subjects of this prospective study were 162 (75 men, 87 women) residents who attended a health examination in Yakumo town in Hokkaido, in 2012 and re-attended at least once while 2013 to 2015. Serum samples were collected in 2012 and serum miRNA were measured by qRT-PCR. We used a short version of the Mini-Mental State Examination (SMMSE) to screen cognitive function, and calculated the change in SMMSE score per year. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) of serum miRNA levels for cognitive decline (decrease of greater than 0.5 points per year) using the lowest tertile group of miRNAs as the reference by logistic regression analysis. Results: The mean age and change in SMMSE score of the subjects was 63.9±9.6 years and -0.03±1.19 points. Odds ratios (ORs) for cognitive decline were significantly higher in the highest tertile of serum miR-221 (OR = 3.24, 95%CI=1.20-8.72) and miR-222 (OR = 4.01, 95%CI=1.36-11.80) even if confounding factors were adjusted. Conclusions: High serum levels of miR-221 and -222 were significantly associated with cognitive decline. Key messages: High serum levels of miR-221 and -222 may be potential candidate biomarkers for prediction of cognitive decline.